Pengajaran Aqidah Ahl Al-Sunnah Wa Al-Jam±’ah di Tatar Sunda pada Abad XIX: Tinjauan Buku Teologi dalam Naskah Sunda Islami - Nurman Kholis (Jurnal Lektur Keagamaan, 2015)
It is widely known that identification of manuscripts on the attributes of Allah and His massanger (Rasul) particularly written in Sundanese Language work of Umm al-Barahim was not being well explored until the end of 20th century. I. Syarief Hidayat, a Padjajaran University professor, then carried out a dissertation research on this issue in 2007 and published it with the title Teologi dalam Naskah Sunda Islami (Theology in Sundanese Islamic Manuscript). In his book, Hidayat suggests that ahlus sunnah wal jama’ah (ASWAJA) as a moderate theology in Islam should be maintained and strengthened in Indonesia. His suggestion could be implemented by optimalizying Islamic ancient texts studies especially in the theme of tauhid or kalam in order to enlighten the urgent need for maintaining ASWAJA teology in current Islamic world.